Functional disability of adult individuals with spinal cord injury and its association with socio-demographic characteristics (Revista Latino-Americana de Enfermagem, 2012)
The aim was to investigate the Functional Disability degree in adults with spinal cord injury and its association with socio-demographic characteristics. The Barthel Index was used and 75 subjects answered a questionnaire with socio-demographic variables. The Chi-Square, Cronbach's Alpha and Fisher tests were used in the analysis. The mean age was 42.23 years. Cronbach's Alpha for the Barthel Index was 0.807. The activities that were more difficult to perform were Climbing and Descending Stairs (92%) and Walking (82.7%). The mean Barthel Index score was 64 points. The tests of association demonstrated values with p>;0.05. Even though this population demonstrated a low degree of dependency and no association was identified between the socio-demographic variables and Functional Disability, the study contributes to nursing care for individuals with spinal cord injury, considering the limitations the condition imposes on their self-care.